Effect of Curcumin (Curcuma xanthorriza) and Red Ginger (Zingiber officinale var. rubrum) Ethanol Extract on Improvement of Mice Sperm Quality Exposed by Monosodium Glutamate - Aprilia, Niken Herny Lidya Aprilia; Rahayu, Sri; Marhendra, Agung Pramana Warih (Graduate School, Universitas Brawijaya, 2024)
Temulawak (Curcuma xanthorriza) and red ginger (Zingiber officinale var. rubrum Theilade) contain antioxidant compounds that play an important role in inhibiting the negative effects of the excessive administration of free radicals. Excessive free radicals affect the spermatogenesis process. Which results in decreased sperm quality. This research determined the effect of administering ethanol extract of ginger and red ginger on the sperm quality of mice exposed to MSG. This study used 25 male mice (Mus musculus), aged 2.5 – 3 months and weighing 25 – 30 g, which were randomly divided into five groups: P0 (control), P1 MSG 4 mg.g-1 bw, P2 MSG 4 mg.g-1 bw and C. xanthorriza extract 0.2 mg.g-1 bw, P3 MSG 4 mg.g-1 bw and Z. officinale extract 0.4 mg.g-1 bw, P4 4 mg.g-1 bw, and a combination of C. xanthorriza extract 0.1 mg.g-1 bw and Z. officinale extract 0.2 mg.g-1 bw, MSG, and all extracts were administered orally for 30 days. On the 31st day, the mice were dissected, and epididymis was collected for sperm quality analysis, such as motility, viability, abnormality, and spermatozoa concentration. Subsequently, the sperm quality data were analyzed using One-way ANOVA through the SPSS 16.0 program for Windows (P<0.05), followed by Tukey's Honestly Significant Difference (HSD) test. The addition of both single and combination from C. xanthorriza and Z. officinale can ameliorate motility, viability, and spermatozoa compared with the group that was only given by MSG. Thus, adding temulawak (C. xanthorriza) and red ginger (Z. officinale) ethanolic extract can also ameliorate the mice's sperm quality. Keywords: C. xanthorriza, MSG, sperm quality, Z. officinale